Editor’s Note - Terdudomtham, Thamavit (Journal of Contemporary Social Sciences and Humanities, 2025)
As in launching the first Issue of RJSH, Dr. Arthit Ourairat, the President of Rangsit University wrote “the RJSH’s mission and identity: not to be just another ‘publish-or-perish’ publication for tenure-seeking scholars, but to help lead the rightful return of intellectualism to its respected place in society”. We, as the new publication team of the RJSH journal, intend to improve this journal quality to act as a medium for presenting new researches with frontier knowledge and new ideas for our society. To be more focus, the scope of this journal is intended to cover the following areas: Social Science (Criminal Justice, Economics, Social Innovation, and Political Science), Humanity (History, Language, Arts & Design), and interdisciplinary studies in Humanity and Social Science. In this issue, we are so pleased that many articles are from the ASEAN countries; Malaysia, Indonesia, Vietnam and Thailand. The Association of Southeast Asian Nations (ASEAN) has been established since 1967. The ASEAN countries have cooperated in politics, economics, and culture, including academics for several decades. We hope that the ASEAN cooperation will be strengthened further. In addition, this issue also has an interesting paper from Nigeria. Let us go through all six articles provide some discussion and information to the readers. In the first article of this current issue, Siti Nurul Iman Muhamad Naim and Idris Mansor studied the classic theatrical script of Tenggelamnya Kapal Van Der Wijck, a Malay-Arabic literary script. It contributes to the Malay-Arabic literary translation and script translators of classical theatre dialogues.